2022
DOI: 10.1108/he-06-2021-0095
|View full text |Cite
|
Sign up to set email alerts
|

Capacity issues in primary health care implementation: examples from Ghana

Abstract: PurposeResources as well as the capacity to employ them judiciously may well be the key to the attainment of the SDGs and other related health goals through primary health care (PHC). Within this PHC framework, however, the source of resources for PHC as well as the systems for managing these associated resources remain unclear, complex and lack substantive integration systems of implementing ministries, departments and agencies (both local and international) in Ghana. These issues are addressed by this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
2
1
Order By: Relevance
“…Also, majority 94.3% agreed that medical students need to learn sexual knowledge including contraceptive methods, 2.9% disagreed and 2.9% did not answer. In this study the attitude of thirdyear medical students towards contraceptive use was good/positive, however, this was not in line with the research done [26], [29]- [32] at the University of Ghana which showed that respondents had a negative/bad attitude about contraceptives.…”
Section: Threecontrasting
confidence: 91%
“…Also, majority 94.3% agreed that medical students need to learn sexual knowledge including contraceptive methods, 2.9% disagreed and 2.9% did not answer. In this study the attitude of thirdyear medical students towards contraceptive use was good/positive, however, this was not in line with the research done [26], [29]- [32] at the University of Ghana which showed that respondents had a negative/bad attitude about contraceptives.…”
Section: Threecontrasting
confidence: 91%
“…That only denotes the beginning of the policymaking process. The model's stages are linked to each other like links in a chain cycle (Appiah-Agyekum et al, 2022). As Bertram, Maleki and Karsten (2019) noted, no policy decision or solution is ever final.…”
Section: Government Policy Cyclementioning
confidence: 99%
“…typically serve as the basis for future policy choices (Appiah-Agyekum et al, 2022;Cagnin, 2017). This is done by carefully reviewing all of the information gleaned from evaluating the policy's outcomes (Mügge and Alenda-Demoutiez, 2019).…”
mentioning
confidence: 99%